Prolapsed uterus - a case study - P.PRIYADARSHINI (International Journal of Pharma and Bio Sciences, 2017)
Uterine prolapse is a condition in which a woman’s uterus (womb) sags or slips out of its normal position. It is a common general problem in which 50% of parous women have some degree of prolapse and 10-20% of these cause symptoms. Pelvic organ prolapse is very frequent; one out of nine women will need a surgery to repair her uterine prolapse. Existing facts on uterine prolapse do not show exactly how many women are affected. However, various studies indicate that it is a common condition and that women face an increased risk as they age. Uterine prolapse can happen to women of any age, but it often affects postmenopausal women who’ve had one or more vaginal deliveries. Weakening of the pelvic muscles that leads to uterine prolapse can be caused by: Damage to supportive tissues during pregnancy and childbirth, Effects of gravity, Loss of estrogen, Repeated straining over the years. If you have mild uterine prolapse, treatment usually isn’t needed. But if uterine prolapse makes you uncomfortable or disrupts your normal life, you might benefit from treatment.